Optimized planar microwave antenna for nitrogen vacancy center based sensing applications - Opaluch, Oliver Roman; Oshnik, Nimba; Nelz, Richard; Neu, Elke (Nanomaterials, 2021)
Individual nitrogen vacancy (NV) color centers in diamond are versatile, spin-based quantum sensors. Coherently controlling the spin of NV centers using microwaves in a typical frequency range between 2.5 and 3.5 GHz is necessary for sensing applications. In this work, we present a stripline-based, planar, Ω-shaped microwave antenna that enables one to reliably manipulate NV spins. We found an optimal antenna design using finite integral simulations. We fabricated our antennas on low-cost, transparent glass substrate. We created highly uniform microwave fields in areas of roughly 400 × 400 µm2 while realizing high Rabi frequencies of up to 10 MHz in an ensemble of NV centers.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Diamond; Microwave antenna; Nitrogen vacancy centers; Spin manipulation